HUBUNGAN KEPEMIMPINAN TRANSFORMASIONAL, WORK-LIFE BALANCE DAN LINGKUNGAN KERJA NON FISIK TERHADAP DISPLIN KERJA - Arifin, Suryana; Rizana, Dani (Politeknik Sawunggalih Aji, 2024)
This study aims to determine the effect of transformational leadership, work-life balance, and non-physical work environment on the work discipline of BPS Kebumen employees. The problem raised in this study is the effect of transformational leadership, work-life balance, and non-physical work environment on the work discipline of BPS Kebumen employees, with the aim of knowing how much influence transformational leadership, work-life balance, and non-physical work environment have on discipline BPS Kebumen employees work partially or simultaneously. Collecting data using a questionnaire with a Likert scale and a total sample of 46 respondents. The sampling technique used in this research is saturated sampling. The hypothesis was tested using multiple regression analysis techniques, t test, f test and the coefficient of determination using SPSS for windows version 25. The results of this study indicate that transformational leadership partially has a significant effect on work discipline, work-life balance partially has a significant effect on work discipline, non-physical environment partially has a significant effect on work discipline. Transformational leadership, work-life balance, and non-physical work environment simultaneously affect work discipline